TELAAH SIYASAH IDARIYAH TERHADAP IMPLEMENTASI KEBIJAKAN BADAN PERTANAHAN NASIONAL TENTANG PEMUKIMAN PENDUDUK KAWASAN HUTAN LINDUNG DI KELURAHAN TAMAONA - Samsiah, Risky Fausia; Risal, M. Chaerul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
The aim of this research is to study siyasah idariah on the implementation of the National Land Agency (BPN) policy regarding residential areas in protected forest areas in Tamaona Village, the issues raised in this paper are regarding the implementation of the National Land Agency related to protected forests and the views of siyasah idariah regarding the implementation of the Land Agency National. This research is field research using qualitative analysis with a normative syar'i and empirical juridical approach. Data collection methods were carried out by means of interviews, observation and documentation. The results of this research show that the implementation of the National Land Agency has carried out a regional mapping process for protected forests in accordance with SK 362 of 2019 and the siyasah idariah view regarding diwan work flow related to land, especially protected forests, is in line with the National Land Agency which does not grant permits to communities. Those who build in protected forest areas must make regulations in accordance with Allah SWT's rules to protect their creation. However, what is an inhibiting factor in implementing the mapping policy carried out by BPN is that there are still people who build in protected forest areas who do not comply with the administration. This is reinforced by people who build without the knowledge of the National Land Agency, so that BPN takes action to change the function of the land.